Determination of Water Content in Direct Resin Composites Using Coulometric Karl Fischer Titration - Faria-e-Silva, André; Heckel, Lea; Belli, Renan; Lohbauer, Ulrich (Materials, 2022)
This study evaluated the water content and sorption of direct composites over 60 days using coulometric Karl Fischer titration (KFT). Plate-shaped specimens (10 × 10 × 1 mm3 of thickness) were built up using the composites Clearfil Majesty Posterior (CM), Grandio SO (GS), and Filtek Supreme XT (FS). Water contents were determined in non-stored specimens (control) or after storage in distilled water for up to 60 days (n = 5). The amount of water transferred from the specimens heated at 200 °C (isothermal mode) was measured in the Coulometer. The water content of non-stored specimens ranged from 0.28 to 1.69 wt% (5.6 to 31.2 μg/mm3) for GS and FS, respectively. The highest values of water sorption were observed for FS (25.3 μg/mm3 after 60 days). GS and CM showed similar water sorption after 60 days (≈9 μg/mm3), but an ultimate higher water content was observed for CM (0.9 wt%; 22.0 μg/mm3) than GS (0.7 wt%; 14.8 μg/mm3). Except for CM, no significant water sorption was observed between 21 and 60 days of storage. Since all composites presented some base water content, water sorption data alone do not account for the ultimate water content in direct resin-based composites.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Karl Fischer titration; resin composite; water sorption